Research on Linear Fractional Town Traffic Flow Model Tactic - Zhao, Chun Na (Transactions on Engineering and Computing Sciences, 2016)
Traffic flow is a worldwide problem. It has many influencing factors and it is the complex system. Fractional calculus is a powerful tool for dealing with complex systems. Fractional calculus is a direct way of extending traditional integer order calculus, which allows the order to be a fraction. Fractional order model achieves better results than the integer order model. A linear fractional order model based on Grunwald–Letnikov’s definition for traffic flow is proposed in this paper. City road traffic flow system is composed of a large number of complex dynamic behaviors of traffic participant. It is a highly nonlinear and non-stationary complex system. Firstly, fractional order calculus is introduced. Then the linear fractional order traffic flow model is proposed based on fractional calculus. The fractional order parameters can be determined by a large number of data and mathematical statistics method. The proposed model was simulated and applied to actual Linghai town road traffic flow. The practicability and effectiveness of the method have been validated.